2019
DOI: 10.3390/su11143818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental and Ecological Impacts of the Leading Large-Scale Reservoir on the Upper Reaches of the Yellow River

Abstract: Large-scale reservoirs have played a significant role in meeting various water demands and socio-economic development, while they also lead to undeniable impacts on the environment and ecology. The Longyangxia reservoir located on the Yellow River is the first large-scale reservoir on the upper Yellow River with a control area of 18% of the entire Yellow River Basin. Since it was put into operation in 1987, it has made great contributions to the national economy for over 30 years. In this study, the socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The catches of the current survey and previous studies indicated a low top–down control. Previous studies report low fish species number and fish biomass with very limited planktivorous fishes in alpine cascade reservoirs ( Tang and He, 2013 ; Wang H. et al, 2016 ; Qiu et al, 2019 ). Analysis of the biomass, abundance, and distribution of the catches showed that Hypomesus olidus , Gymnocypris eckloni Herzensten, Triplophysa scleroptera , and Schizopygopsis pylzovi Kessler were the most dominant species ( Tang and He, 2013 ; Qiu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The catches of the current survey and previous studies indicated a low top–down control. Previous studies report low fish species number and fish biomass with very limited planktivorous fishes in alpine cascade reservoirs ( Tang and He, 2013 ; Wang H. et al, 2016 ; Qiu et al, 2019 ). Analysis of the biomass, abundance, and distribution of the catches showed that Hypomesus olidus , Gymnocypris eckloni Herzensten, Triplophysa scleroptera , and Schizopygopsis pylzovi Kessler were the most dominant species ( Tang and He, 2013 ; Qiu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies report low fish species number and fish biomass with very limited planktivorous fishes in alpine cascade reservoirs ( Tang and He, 2013 ; Wang H. et al, 2016 ; Qiu et al, 2019 ). Analysis of the biomass, abundance, and distribution of the catches showed that Hypomesus olidus , Gymnocypris eckloni Herzensten, Triplophysa scleroptera , and Schizopygopsis pylzovi Kessler were the most dominant species ( Tang and He, 2013 ; Qiu et al, 2019 ). The dominant taxa, including Schizothorax and Triplophysa in the studied cascade reservoir system, were mainly omnivorous fish.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The construction of reservoirs not only brings huge social and economic benefits to the YRB in terms of water storage, power generation, flood control and irrigation, but also can change the fluvial morphology and the spatial-temporal distribution of water resources. This directly or indirectly affects the ecological environment (Qiu et al, 2019). Reservoir dispatch management has important practical significance for further improving the ecological health of the YRB (Bai et al, 2020).…”
Section: Ecological Degradation Index Systemmentioning
confidence: 99%